2016
DOI: 10.1111/eff.12278
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in metabolic rate and swimming performance in pink salmon (Oncorhynchus gorbuscha): the effect of male secondary sexual traits

Abstract: Do secondary sexual traits, such as large dorsal hump and hooked snout, decrease the swimming efficiency of male pink salmon during freshwater migration? This is the first study to address the effects of secondary sexual traits in pink salmon on oxygen uptake and swimming capacity. We conducted a laboratory experiment using a swimming respirometer and a field study using electromyogram (EMG) telemetry in the Shibetsu River, Hokkaido, Japan. We compared the relationship between MO2 (mg O2·kg−1·h−1) and swimming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Salmon males mature on average earlier than females (Fleming & Einum 2011) and the vgll3 locus is associated with freshwater maturation in male parr (Debes et al 2021;Verta et al 2020). Other studies in salmonids have found sex differences in the performance of 2+ yearold or mature individuals, including a higher aerobic scope, but not SMR, and a higher cost of swimming in males than in females (Clark et al 2011;Makiguchi et al 2017;Archer et al 2020). The lack of sex differences in metabolic phenotypes in our study both across and within age-at-maturity genotypes, therefore, supports the conclusion that sex-dependent lifehistory variation is not reflected in metabolic rates during the juvenile stage, as suggested by a few other studies (Regnier et al 2015;Prokkola et al 2021;Åsheim et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Salmon males mature on average earlier than females (Fleming & Einum 2011) and the vgll3 locus is associated with freshwater maturation in male parr (Debes et al 2021;Verta et al 2020). Other studies in salmonids have found sex differences in the performance of 2+ yearold or mature individuals, including a higher aerobic scope, but not SMR, and a higher cost of swimming in males than in females (Clark et al 2011;Makiguchi et al 2017;Archer et al 2020). The lack of sex differences in metabolic phenotypes in our study both across and within age-at-maturity genotypes, therefore, supports the conclusion that sex-dependent lifehistory variation is not reflected in metabolic rates during the juvenile stage, as suggested by a few other studies (Regnier et al 2015;Prokkola et al 2021;Åsheim et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of oxygen uptake was measured at least three times at 0.3 FL s -1 , and the lowest value from the trials was used as RMR. After measuring RMR, maximal exercise was achieved using a critical swim speed (U crit ) test based on a protocol described previously (Makiguchi et al, 2017). Briefly, the water flow was increased to 0.9 FL s -1 and the fish were made to swim for 15 min.…”
Section: Respirometry and Swimming Experimentsmentioning
confidence: 99%
“…The relationship between metabolic rate and locomotor performance has been particularly well studied in fish, due to the logistical simplicity of swim‐tunnels. Across fish species, increasing swim‐tunnel water velocity is associated with elevated metabolic rates (Figure B; Gamperl et al ; Fitzgibbon et al ; Li et al , ; Dickson et al ; Fu et al ; Fangue et al ; Penghan et al ; Nowell et al ; Tudorache et al ; Makiguchi et al ). Therefore, individuals with a higher standard metabolic rate (i.e., demand‐side energy elevation) or lower maximum metabolic rate (i.e., supply‐side energy reduction) typically have reduced swimming performance (Cano and Nicieza ).…”
Section: Defining Bioenergetics‐aopmentioning
confidence: 99%